RASIONALITAS EKONOMI ISLAM DALAM PERSPEKTIF MIKRO - Siti Maryam; Zaskia Dwi Lestari; Famela An-Umilah; Riani Azzahra; M Yusuf Bahtiar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to explain the concept and system of Islamic economics as a comprehensive solution (kaffah), integrating the dimensions of faith, sharia, and morality in every economic activity to achieve happiness in this world and the hereafter (falah). This study uses a library research approach by critically reviewing and in-depth review of various relevant sources, such as books and scientific journals. Data is analyzed descriptively to provide a systematic overview of the principles of Islamic economics. The research demonstrates that Islamic economics is a social science built on a foundation of revelation (the Qur'an and Sunnah). Unlike capitalist systems, Islam does not separate economics from ethics. Humans are viewed as trustees (wali) who have the freedom to strive but are bound by moral constraints and sharia law. This system also recognizes a broader concept of rationality, encompassing devotion to the Creator and the welfare of others. Islamic economics is an integral system that unites material and spiritual aspects. Economic success from an Islamic perspective is measured not only by financial profit but also by upholding justice, honesty, and social balance to achieve sustainable human well-being.